Pengembangan dan Kesiapterapan Jiwa Kewirausahaan pada Siswa Sekolah Dasar - Marliani Herlina; Udin Saefudin Sa’ud; Disman Disman; Wahyu Sopandi; Nuke Puji Lestari Santoso (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2020)
Elementary school students in general are still learning traditionally. Especially elementary school students learn entrepreneurship to train to create value innovations that are valuable independently. However, in this 4.0 era, many elementary students still run entrepreneurship in the traditional way by producing physical works, this is certainly because elementary school students do not experience development with the interference of technology. What should be elementary school students should have started to know technology early on. So, the purpose of this research is to empirically discuss how elementary school students are able to learn entrepreneurship digitally from an early age. With the iLearning method elementary school students are able to develop with a blend of technology 4.0 to create innovative results visually. The presence of the SEP (School Enrichment Program) system which is a bridge for elementary school students in learning entrepreneurship through learning so that they can improve their quality early on. In addition, the gamification techniques that exist in the system make elementary school students significantly more motivated in entrepreneurial learning. The sample data test results show that Cronbach's Alpha 0.702> 0.6 on the SEP system is significantly reliable.